1982
DOI: 10.1002/mrd.1120060305
|View full text |Cite
|
Sign up to set email alerts
|

Sperm tail entry into the mouse egg in vitro

Abstract: Cumulus‐free mouse eggs were placed on microscope slides and inseminated with capacitated mouse spermatozoa. Fertilization could then be observed through the phase contrast microscope and recorded by time‐lapse cinematography. Following the penetration of the fertilizing spermatozoon through the zona pellucida and the fusion of the sperm head with the vitelline membrane, the entire sperm tail gradually entered the vitellus. The time required for tail incorporation into the vitellus as measured in 49 eggs varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…) Notwithstanding differences in its position at the start of incorporation,the sperm tail is usually incorporated into the vitellus in its entirety whether penetration has occurred in vitro or in vivo. (Some instances of incomplete incorporation have been noted during in vitro fertilization in the mouse and hamster [Gaddum-Rosse et al, 1982;Yang et al, 1972;Yanagimachi, 19811. ) Only two of the mammalian species studied so far are exceptions to this generalization: the Chinese hamster and the field vole (Austin and Walton, 1960;Pickworth et al, 1968;Yanagimachi et al, 1983).…”
Section: Incorporation Of the Sperm Flagellummentioning
confidence: 94%
See 4 more Smart Citations
“…) Notwithstanding differences in its position at the start of incorporation,the sperm tail is usually incorporated into the vitellus in its entirety whether penetration has occurred in vitro or in vivo. (Some instances of incomplete incorporation have been noted during in vitro fertilization in the mouse and hamster [Gaddum-Rosse et al, 1982;Yang et al, 1972;Yanagimachi, 19811. ) Only two of the mammalian species studied so far are exceptions to this generalization: the Chinese hamster and the field vole (Austin and Walton, 1960;Pickworth et al, 1968;Yanagimachi et al, 1983).…”
Section: Incorporation Of the Sperm Flagellummentioning
confidence: 94%
“…Although mouse eggs undergoing in vitro fertilization do not display such prominent surface movements as rat eggs, there is nonetheless a n interesting change detectable by time-lapse cinematography: an increase in the rate of motion of granular components within the egg cytoplasm after fusion (Gaddum-Rosse et al, 1982). Furthermore, Waksmundzka et al (1984) have observed that the surface of fertilized mouse eggs changes from smooth to slightly undulate about 7-10 hr after activation.…”
Section: Surface Movements Of the Vitellusmentioning
confidence: 95%
See 3 more Smart Citations